Isolation of apoptosis-related genes in A549 lung cancer cell line treated with gelam honey / Siti Nadiah Che Bahrun - Che Bahrun, Siti Nadiah (2013)
Differentially expressed genes in the A549 lung cancer cells identified using GeneFishing™ DEG Premix Kit. These genes then were further analysed by cloning and sequencing. The methods were able to successfully clone and identify differentially expressed gene and further validation is required to validate the expression of this gene in A549 cells upon treatment with honey either by Northern blot or real-time PCR. Numerous studies on the benefits of honey have been reported in the literature. They were also reported to cause apoptosis in cancer cells.